The effect of daily life activities on intraocular pressure related variations in open-angle glaucoma - Kevin Gillmann (Nature Portfolio, 2021)
Abstract The recent advent of continuous intraocular pressure (IOP) telemetry has led to an increased awareness of the importance of IOP fluctuations, and theories have emerged that IOP variations could play as much a role in glaucoma progression as the mean level of IOP. The aim of the present study was to evaluate the direct effect of common daily activities on IOP-related profiles. Primary open-angle glaucoma and glaucoma suspect patients were prospectively enrolled from specialist clinics at the University of California San Diego (UCSD), USA. Patients were fitted with a SENSIMED Triggerfish (TF) contact lens sensor (CLS) and were instructed to return to their usual daily activities for 24 h. They were asked to record each specific activity or event in a diary. The protocol was repeated twice. The following events were recorded: “walking/cycling”, “resistance training”, “yoga/meditation”, and “emotional stress”. CLS measurements recorded 60-to-30 min prior to each event were used as a baseline reference, and all IOP-related fluctuations for 120 min after the start of each event were reported in relation to this reference. Forty relevant events from 22 CLS recordings in 14 patients were retrieved from the diaries. Walking/cycling (n = 10) caused a small but statistically significant elevation of the IOP-related profile during the activity (p = 0.018). Resistance training (n = 11) caused a persistent elevation of the IOP-related profile from the onset of the activity (p = 0.005) through 120 min after the activity was stopped (p = 0.007). Yoga/meditation (n = 4) caused a sustained drop in the IOP-related profiles through to 120 min, although this was not statistically significant (p > 0.380). Emotional stress (n = 13) was associated with a gradual elevation of the IOP-related profile from the start of the stressful stimulus. Both early and late variations were statistically significant (p = 0.038 and p = 0.021, respectively). The present study suggests that emotional stress and resistance training may be associated with persistent IOP-related profile elevation.